IL-15 Overcomes Hepatocellular Carcinoma-Induced NK Cell Dysfunction - Easom, Nicholas J. W.; Stegmann, Kerstin A.; Swadling, Leo; Pallett, Laura J.; Burton, Alice R.; Odera, Dennis; Schmidt, Nathalie; Huang, Wei-Chen; Fusai, Giuseppe; Davidson, Brian; Maini, Mala K. (Frontiers in Immunology, 2018)
NK cells have potent anti-tumour capacity. They are enriched in the human liver, with a large subset specialised for tissue-residence. The potential for liver-resident versus liver-infiltrating NK cells to populate, and exert anti-tumour functions in, human liver tumours has not been studied. We examined liver-resident and liver-infiltrating NK cells directly ex vivo from human hepatocellular carcinomas (HCC) and liver colorectal (CRC) metastases, compared with matched uninvolved liver tissue. We found that NK cells were highly prevalent in both HCC and liver CRC metastases, although at lower frequencies than unaffected liver. Up to 79% of intratumoral NK cells had the CXCR6+CD69+ liver-resident phenotype. Direct ex vivo staining showed that liver-resident NK cells had increased NKG2D expression compared to their non-resident counterparts, but both subsets had NKG2D downregulation within liver tumours compared to uninvolved liver. Proliferation of intratumoral NK cells (marked by Ki67) was selectively impaired in those with the most marked NKG2D downregulation. Human liver tumour NK cells were functionally impaired, with reduced capacity for cytotoxicity and production of cytokines, even when compared to the hypo-functional tissue-resident NK cells in unaffected liver. Co-culture of human liver NK cells with the human hepatoma cell line PLC/PRF/5, or with autologous HCC, recapitulated the defects observed in NK cells extracted from tumours, with downmodulation of NKG2D, cytokine production and target cell cytotoxicity. Transwells and conditioned media confirmed a requirement for cell contact with PLC/PRF/5 to impose NK cell inhibition. IL-15 was able to recover anti-tumour functionality in NK cells inhibited by in vitro exposure to HCC cell lines or extracted directly from HCC. In summary, our data suggest that the impaired anti-tumour function of local NK cells reflects a combination of the tolerogenic features inherent to liver-resident NK cells together with additional contact-dependent inhibition imposed by HCC itself. The demonstration that IL-15 can recover hepatic NK cell function following tumour exposure supports its inclusion in immunotherapy strategies.